2016
DOI: 10.1016/j.jmii.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunomodulatory supplementation with Lactobacillus rhamnosus on airway inflammation in a mouse asthma model

Abstract: LGG had an anti-inflammatory effect on OVA-induced airway inflammation and might be an additional or supplementary therapy for allergic airway diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 57 publications
8
64
0
4
Order By: Relevance
“…The specific mechanism of action of NCC 2287 during allergy treatment is not known. In general, probiotic effects on allergic inflammation are mainly attributed to their capacity to increase the CD4 + CD25 + Foxp3 + regulatory T‐cell pool in peripheral lymph nodes , to decrease sensitization efficacy and/or to modulate cytokine expression . While T regulatory cells have been associated with decreased esophageal eosinophilia in another EoE model , it has recently been shown that other regulatory mechanisms may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanism of action of NCC 2287 during allergy treatment is not known. In general, probiotic effects on allergic inflammation are mainly attributed to their capacity to increase the CD4 + CD25 + Foxp3 + regulatory T‐cell pool in peripheral lymph nodes , to decrease sensitization efficacy and/or to modulate cytokine expression . While T regulatory cells have been associated with decreased esophageal eosinophilia in another EoE model , it has recently been shown that other regulatory mechanisms may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with LGG has been shown to decrease MMP9 expression in lung tissue and to inhibit inflammatory cell infiltration. In addition, in OVA-sensitized mice, LGG reduced OVA-specific IgE levels in serum, suppressed the airway hyper-responsiveness to methacholine and decreased the number of infiltrating inflammatory cells and Th2 cytokines in bronchoalveolar lavage fluid and serum (31). Similar results have been reported with other probiotics (32).…”
Section: Probiotics For Prevention Of Asthma and Eczemamentioning
confidence: 99%
“…113 Oral administrations of Lactobacillus rhamnosus attenuates OVA-induced airway inflammation. 114 Also, L. casei and L. acidophilus diminish arthritic symptoms in the collagen-induced arthritis model by inhibiting proinflammatory cytokines and inducing anti-inflammatory cytokines. 115 …”
Section: Microbiota-target Treatmentmentioning
confidence: 99%